Production Optimization and Characterization of Phytohormone Indole Acetic Acid by Pseudomonas fluorescence - Jeyanthi, V (International Journal of Pharmaceutical & Biological Archive, 2013)
Production Optimization and Characterization of Phytohormone Indole Acetic Acid by Pseudomonas fluorescence